Azaacene diradicals based on Non-Kekulé meta-quinodimethane with large two-photon cross-sections in the infrared spectral region - Fuchs, Kathleen; Oberhof, Nils; Sauter, Gabriel; Pollien, Audrey; Brödner, Kerstin; Rominger, Frank; Freudenberg, Jan; Dreuw, Andreas; Tegeder, Petra; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2024)
Non-Kekulé quinoidal azaacences m-A (1a,b) were synthesized and compared to their para- and ortho-quinodimethane analogues. m-Adisplay high diradical characters (1b: y0 = 0.88) due to their meta-quinodimethane (m-QDM) topology. Electron paramagnetic, nuclear magnetic resonance spectroscopies and supraquantum interference device measurements in combination with quantum-chemical calculations revealed singlet ground states for m-A with singlet-triplet gaps ΔEST (0.13-0.25 kcal mol-1) and thermally populated triplet states. These non-Kekulé structures are over all void of zwitterionic character and possess record high two-photon absorption cross sections over a broad spectral range in the near-infrared.
Gesehen am 19.09.2024